Transforming Lives: Olubunmi Oke's Journey with Farmers Outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this video, Olubunmi Tayo Oke shared how Radio IITA’s outreach program exposed her to revolutionary techniques in cassava stem cutting and seed multiplication which dramatically enhanced her farm’s productivity.